Nomenclature of Chinese Street Food Names in Malaysia : A Scalar Analysis - Hongxiang, Zhu; Ang, Lay Hoon; Nor Shahila, Mansor; Lam, Kai Chee (SAGE Publications Inc, 2023)
This study examines how the nomenclature of street food names includes trans-local, trans-regional, and trans-national scales in local language resources. The study adopts a qualitative case study on street food names in Malaysia. The study sample comprised 856 street food names collected in Kuala Lumpur. The food nomenclature framework and the concepts of translocal, trans-regional, and trans-national scales were adopted to elicit the data. It was found that: (i) there are more complex combinations based on ingredient, cooking method, food attribute, commemorative aspect, and good name; (ii) there are scale-making ways, via the presentation and the transliteration of street food elements. In conclusion, the nomenclature of street food names labels Malaysia as a multiscalar locality in which trans-local, trans-regional, and trans-national scales can be discerned. Thus, this study reveals how nomenclature shapes and is shaped by geographical scales. Therefore, it contributes to the nomenclature of food and place marketing.